POLA KEGIATAN PEREKONOMIAN - Dasopang, Nursania (Islamic Circle, 2020)
The pattern of economic activity is a form of economic activity whichdoes by people or even a country to improve the quality of the economy from time to time and is carried out continuously. This pattern will always be monitored in terms of strengths and weaknesses which will use it to be a reference to design a better pattern of economic activity. The pattern of economic activity will cover many vital topics such as money, trade and specialties that can be carried out at the economic level of the family to the state. Therefore, each pattern of economic activity will be different depending on the actors of economic activity themselves. Especially for the country, this pattern of economic activity will be highly visible from the monetary policy undertaken. How is the financial management system, revenue flow circulation, and market mechanisms regulated by the government. Therefore, the country will continue to carry out monetary reforms to create a pattern of good economic activity for mutual prosperity.